Sensitivity and Specificity of the Mini-Mental State Examination for Identifying Dementia in the Oldest-Old: The 90+ Study - Kahle-Wrobleski, Kristin; Corrada, Maria M.; Li, Bixia; Kawas, Claudia H. (Journal of the American Geriatrics Society (JAGS), 2007)
OBJECTIVES: To evaluate the sensitivity and specificity of the Mini‐Mental State Examination (MMSE) in identifying dementia in the oldest‐old when stratified by age and education. DESIGN: Cross‐sectional. SETTING: Research clinic and in‐home visits. PARTICIPANTS: Population‐based sample of adults aged 90 and older (n=435) who are enrolled in the 90+ Study, a longitudinal, population‐based study. MEASUREMENTS: Neurological examination to determine dementia diagnosis, MMSE, and demographic data. RESULTS: Receiver operating characteristic (ROC) analyses indicated that the MMSE had high diagnostic accuracy for identifying dementia in subjects aged 90 and older across different age and education groups (area under the ROC curve values ranged from 0.82 to 0.98). A range of possible cutoff values and corresponding sensitivity and specificity are provided for the following age groups: 90–93, 94–96, and ≥97. Age groups were subdivided by educational attainment (≤high school, vocational school or some college, college degree or higher). In subjects aged 90 to 93 with a college degree or higher, the suggested MMSE cutoff score is ≤25 (sensitivity=0.82, specificity=0.80). In those aged 94 to 96 with a college degree or higher, the suggested cutoff is ≤24 (sensitivity=0.85, specificity=0.80). Those aged 97 and older with an education of high school or less had the lowest suggested cutoff ≤22 (sensitivity=0.80, specificity=0.76). CONCLUSION: Overall, the MMSE had good sensitivity and specificity across all age and educational groups. Optimal cutoff points were lower in the older age groups and those with less education, primarily to preserve specificity. This screening instrument is appropriate for use with the oldest‐old.